Nothing Really Matters: Evaluating Demand-Side Moderators of Age Discrimination in Hiring - Axana Dalle; Louis Lippens; Stijn Baert (Institute of Labor Economics (IZA), 2023)
As age discrimination hampers the OECD's ambition to extend the working population, an efficient anti-discrimination policy targeted at the right employers is critical. Therefore, the context in which age discrimination is most prevalent must be identified. In this study, we thoroughly review the current theoretical arguments and empirical findings regarding moderators of age discrimination in different demand-side domains (i.e. decision-maker, vacancy, occupation, organisation, and sector). Our review demonstrates that the current literature is highly fragmented and often lacks field-experimental evidence, raising concerns about its internal and external validity. To address this gap, we conducted a correspondence experiment and systematically linked the resulting data to external data sources. In so doing, we were able to study the priorly determined demand-side moderators within a single multi-level analysis and simultaneously control multiple correlations between potential moderators and discrimination estimates. Having done so, we found no empirical support for any of these moderators.
Keywords: J71; J23; J14; 330; ageism; hiring discrimination; heterogeneity; literature review; field experiment; administrative data